Upaya Peningkatan Minat dan Rekrutmen Mahasiswa Baru pada Program Studi Pendidikan Jasmani dan Ilmu Keolahragaan Universitas Mulawarman di Kabupaten Berau, Kalimantan Timur - Didik Cahyono; Agung Rahmadani; Rizal Izmi Kusumawijaya (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
This community service program aims to increase student interest and recruitment in the Physical Education and Sports Science Study Program at Mulawarman University in Berau Regency, East Kalimantan. The main problem faced is the low interest of high school students in continuing their studies in physical education and sports science due to limited information regarding study programs, university admission pathways, and career prospects for graduates. The implementation methods included direct academic outreach in schools, career education workshops, sports teaching clinics, and a digital campaign through social media. Evaluation was conducted using pre- and post-test interest questionnaires, teacher interviews, and recording the number of new student applicants. The results of the activity showed a significant increase in student understanding and interest in continuing their studies, as well as an increase in the number of new student applicants from the target schools. These findings indicate that the combination of direct academic promotion and digital campaigns is effective in increasing new student recruitment. The program also succeeded in establishing partnerships between universities and schools as a sustainable measure. This community service activity is recommended for replication in other regions to support equitable access to higher education in physical education and sports science.